2022
DOI: 10.5194/amt-2022-292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance evaluation of the Alphasense OPC-N3 and Plantower PMS5003 sensor in measuring dust events in the Salt Lake Valley, Utah

Abstract: Abstract. As the changing climate expands the extent of arid and semi-arid lands, the number, severity of, and health effects associated with dust events are likely to increase. However, regulatory measurements capable of capturing dust (PM10, particulate matter smaller than 10 µm in diameter) are sparse, sparser than measurements of PM2.5 (PM smaller than 2.5 µm in diameter). Although low-cost sensors could supplement regulatory monitors, as numerous studies have shown for PM2.5 concentration, most of these s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In recent years, commercially available, low‐cost air quality sensors have become common, and regulatory agencies started using them to obtain more granular information on air quality spatial and temporal distribution (Jaffe et al., 2023). However, the accuracy and precision of these sensors need to be characterized (Zheng et al., 2018), the sensors require calibrations (Ardon‐Dryer et al., 2020) and recent work suggests they are unable to accurately characterize coarse particles (>2.5 μm) (Jaffe et al., 2023; Kaur & Kelly, 2023; Rueda et al., 2023) and they still contain spatial gaps. These spatial gaps limit our ability to fully quantify the number and nature of dust events and their subsequent impacts.…”
Section: Large Spatial Gaps In Data Results In Unmonitored Eventsmentioning
confidence: 99%
“…In recent years, commercially available, low‐cost air quality sensors have become common, and regulatory agencies started using them to obtain more granular information on air quality spatial and temporal distribution (Jaffe et al., 2023). However, the accuracy and precision of these sensors need to be characterized (Zheng et al., 2018), the sensors require calibrations (Ardon‐Dryer et al., 2020) and recent work suggests they are unable to accurately characterize coarse particles (>2.5 μm) (Jaffe et al., 2023; Kaur & Kelly, 2023; Rueda et al., 2023) and they still contain spatial gaps. These spatial gaps limit our ability to fully quantify the number and nature of dust events and their subsequent impacts.…”
Section: Large Spatial Gaps In Data Results In Unmonitored Eventsmentioning
confidence: 99%
“…Low-cost detectors, have been shown to be quite unreliable in recording particles with diameters between 2.5µm and 10µm, making their PM10 readings questionable (Jaffe 2023; Karu and Kelly 2023; Kuula et al 2020;Ouimette et al 2022). In particular, both the Plantower and Sensirion sensors used in this study, have been shown to have poor performance during dust-dominated conditions (Kaur and Kelly 2022). The aerosol loading at the locations of the present study is, generally, dominated by fine aerosols, with occasional episodes of wind-blown dust from the Sahara desert.…”
Section: Quality Controlsmentioning
confidence: 89%
“…The Raspberry Pi 3 B+ is powered by a quad-core ARM Cortex-A53 CPU, providing adequate processing power for a variety PM sensors work by having a small fan that draws air through the device and past a laser which detects both the concentration number and size of the particles in the surrounding air. The sensor within the handheld device used is PMS5003 PM sensor which has previously been correlated for use in the real-world [23]. Previous studies have shown that the addition of particulate matter supports the classification of emotions [11].…”
Section: System Architecturementioning
confidence: 99%